Participation in monitoring the 2024 election through election monitoring agencies - Mahyudin Mahyudin; Ansar Suherman; L.M. Azhar Sa'ban; Andy Arya Maulana Wijaya; Harry Fajar Maulana; Abdul Rahim; Eko Satria; Rahmatul Ajhar (Community Empowerment, 2024)
Election observers, Faculty of Social and Political Sciences, Muhammadiyah University of Buton, accredited as an election monitoring institution in Baubau City. The purpose of this election monitoring activity is to ensure that the general election runs smoothly. The method used in this activity is coordination and supervision. The result of this service is that the February 14 2024 voting will not only be a busy time for election participants and election organizers. Election monitoring institutions are also busy with consolidation and training agendas for preparation before going into the field to monitor election implementation. The work of election observers is not only during voting at polling stations. Election observers begin to supervise the election process from the moment the election stage begins. Observers ensure that election organizers carry out all stages and schedules according to what has been determined. Meanwhile, during voting, observers supervise the implementation of voting from the time the polling station opens until it closes. Monitoring is carried out, among other things, regarding voting procedures, vote recapitulation results, including recording findings of suspected fraud, such as money politics and intimidation of voters.